2017
DOI: 10.1097/anc.0000000000000425
|View full text |Cite
|
Sign up to set email alerts
|

Be Sweet to Babies During Painful Procedures

Abstract: Future studies are required to evaluate the effectiveness of this parent-targeted intervention on increasing actual use of pain management in clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(51 citation statements)
references
References 18 publications
3
45
0
2
Order By: Relevance
“…Parents may also benefit from other styles of novel intervention, such as YouTube videos, web pages, and smartphone applications. For example, studies have demonstrated the effectiveness of YouTube videos as a method of knowledge translation targeting parental pain management strategies, 35 explored the utility of web pages as a means of patient pain education, 36 and demonstrated the effectiveness of a smartphone application (Pain Squad+) in engaging adolescents in their own pain management processes. 37 There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Parents may also benefit from other styles of novel intervention, such as YouTube videos, web pages, and smartphone applications. For example, studies have demonstrated the effectiveness of YouTube videos as a method of knowledge translation targeting parental pain management strategies, 35 explored the utility of web pages as a means of patient pain education, 36 and demonstrated the effectiveness of a smartphone application (Pain Squad+) in engaging adolescents in their own pain management processes. 37 There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…The nurses were subsequently asked to individually answer a second questionnaire on their previous knowledge on the use of breastfeeding, SSC and sweet tasting solutions for the relief of neonatal procedural pain, and also to their perception regarding the feasibility, acceptability and usefulness of the instructional video. This instrument, composed of six closed questions and one open question, was adapted from previous studies (16,18) , and required a response time of approximately 10 minutes. Total time for participation on this study was approximately 21 minutes per nurse.…”
Section: Methodsmentioning
confidence: 99%
“…In previous studies, parents of infants hospitalized in neonatal units (16,18) and health professionals who watched the video on YouTube (17) considered it useful, easy to understand and easy to apply in real situations. Nevertheless, the perception of nursing professionals working in Brazilian health services is still unknown, thus justifying the present study that aims: to describe the profile of nurses who work in hospital units that care for newborns; to verify nurses' prior knowledge on breastfeeding, skin-to-skin care and sweet tasting solutions for neonatal procedural pain relief; and to evaluate nurses' perceptions on the feasibility, acceptability and usefulness of the Portuguese version of the "Be Sweet to Babies" video.…”
Section: Introductionmentioning
confidence: 99%
“…Contudo, uma vez que a disseminação online deste e de outros vídeos (Campbell-Yeo et al, 2017, Harrison et al, 2016b em mídias sociais é passiva, os efeitos de sua introdução na rotina de unidades que assistem ao RN ainda são desconhecidos, o que demonstra a necessidade de novos estudos que avaliem o impacto de vídeos instrucionais direcionados ao pais, como o "Seja doce com os bebês", no uso real de medidas analgésicas durante procedimentos dolorosos realizados em RNs (Bueno et al, 2017b;Harrison et al, 2017b).…”
Section: A Tradução Do Conhecimentounclassified
“…Pesquisadores têm demonstrado os benefícios do envolvimento dos pais (Campbell-Yeo; Fernandes; Johnston, 2011; Franck; Oulton; Bruce, 2012; Skene et al, 2012) no manejo da dor neonatal, bem como do uso de vídeos instrucionais como estratégia de TC a pais de lactentes durante a administração de vacinas (Taddio et al, 2014c(Taddio et al, , 2015. No entanto, ainda há recomendações de novos estudos que avaliem o impacto de vídeos instrucionais no contexto do manejo da neonatal (Bueno et al, 2017b;Campbell-Yeo et al, 2017;Harrison et al, 2017b).…”
Section: Justificativaunclassified